A flexible modeling framework for hydraulic and water quality performance assessment of stormwater green infrastructure. (June 2017) - Massoudieh, Arash; Maghrebi, Mahdi; Kamrani, Babak; Nietch, Christopher; Tryby, Michael; Aflaki, Sassan; Panguluri, Srinivas
Abstract: A flexible framework has been created for modeling multi-dimensional hydrological and water quality processes within stormwater green infrastructure (GI) practices. The framework conceptualizes GI practices using blocks (spatial features) and connectors (interfaces) representing functional components of a GI. The blocks represent spatial features with the ability to store water (e.g., pond, soil, benthic sediments, manhole, or a generic storage zone) and water quality constituents including chemical constituents and particles. The hydraulic module can solve a combination of Richards equation, kinematic/diffusive wave, Darcy, and other user-provided flow models. The particle transport module is based on performing mass-balance on particles in different phases, e.g., mobile and deposited in soil with constitutive theories controlling their transport, settling, deposition, and release. The reactive transport modules allow constituents to be in dissolved, sorbed, bound to particles, and undergo user-defined transformations. Four applications of the modeling framework are presented that demonstrate its flexibility for simulating urban GI performance. Highlights: A flexible modeling tool for analysis of green infrastructure performance is introduced. The model allows users to conceptualize green infrastructure with desired complexity level. The tools allows representing hydraulics, particle and constituent transport within GIs. The applicability of the model is demonstrated using four case studies.